Network Management. - Subramanian, Mani. (1900)
Network Management: Principles and Practice provides a balanced presentation of the theoretical background and the practical aspects of network management. Unlike other books that cover only specific network technologies, Mani Subramanian lays the foundation for network management by presenting the background, the technologies, and the tools that all network managers simply must know. He does this by breaking the book down into three parts: PART I provides a background on networking and network technologies such as hubs, routers, bridges, and switches. PART II addresses network management architectures and protocols and then moves on to discuss SNMP management, broadband management, and TMN. PART III focuses on tools to monitor network parameters, network management applications, and solutions to manage networks and systems. Throughout the book, the author intertwines real-world examples based upon his experience in managing, engineering, and operating networks. This text is designed for senior-level or graduate courses in network management, and enables students to move on to the networking industry or to pursue or continue research in the field. It is useful for both computer science and electrical/computer engineering courses in networking.
ADSL Access Network in Overall Network.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books